P-082 INNOVATION IN INGUINAL HERNIA REPAIR. (13th October 2022) - Santilli, O; Santilli, H; Nardelli, N; Scaravonati, R
Abstract: Aim: Innovation is to efficiently use knowledge to improve an existing process for the benefit of users and their environment. The aim is to show different innovations that we are applying in inguinal hernia repair. Material & Methods: We present: 1. data from the first 500 procedures using 5mm articulated instruments. 2. Postoperative sports rehabilitation protocol designed to improve quality of life. 3. Virtual interactive visits (VIV) to teach and learn at a distance allows interaction in the operating room between a specialist and the surgeon in training. Results: The articulated forceps allow angulations in order to reach areas with less pulling force and movements. The accepted benefits of robotics have been achieved without significant cost impact. The sport rehabilitation protocol after laparoscopic hernioplasty does not increase recurrence rate or complications. It probably accelerates the return to regular physical activity, improving the quality of life in the postoperative period. The (VIV) allows us to carry out the training process of specialists from Buenos Aires to Latin America and Spain, ​​modifying and improving the education and training of the new generations. Conclusions: The articulated graspers, the sports rehabilitation protocol, and the virtual interactive visits allow us to innovate in tools, quality of life, and education.